The Power of Teaching Attitudes: Influencing Student Performance at Indanan National High School (Annex) - Amil, Farulyn Ibno; Sakili, Muammar S.; Hayudini, Magna Anissa A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The research, “The Power of Teaching Attitudes of Teachers and Students ‘Performance at Indanan National High School (Annex)” results showed that teachers in English, Mathematics, Science have very high teaching attitudes which were described as excellent along eight dimensions – clarity, enthusiasm, interaction, organization pace disclosure speech and rapport. Nevertheless, despite these favorable attitudes, academic performance in students was reported as being at a “Satisfactory” level and statistical analyses (t-test and ANOVA) found no significant correlation between teachers’ attitudes to teaching and student grades nor across subjects. The results imply that the impact of positive teaching attitude on a conducive learning climate may be overridden by other factors like instruction, students motivation to learn and home background in relation to their influence on academic achievement.  In particular, it sought to investigate the teachers’ attitudes towards students as perceived by students themselves, to assess academic performance of the latter and to test the attitudes that teachers have towards their students whether they have a significant effect on students’ learning outcome. That is, it tried to measure the teachers’ attitudes towards students as perceived by their students, evaluate the learning performance of their students and test if the teachers’ attitudes toward students have an effect on the learning performance of these students.